STUDI HISTORIOGRAFI HADIS MASA MU’ASHIRIN: (Penulisan Sejarah Hadis Pada Abad 11-15 Hijriyyah): Penulisan Sejarah Hadis Pada Abad 11-15 Hijriyyah - halwaini, fiqi (Jurnal El-Hikam, 2024)
This article discusses the historiography of hadith during the Mu'ashirin period of the 11th-15th centuries, from its initial appearance to its development. This research uses qualitative-historical research methods. By using a type of research that is library research. and uses data sources related to the historiography of the Mu'ashirin period. The historiography of hadith in this century is an interesting study to study, because in that century there was a stagnation and in this century hadith also experienced a revival. Where the phase of stagnation and freezing occurred in the 10th century until the beginning of the 14th century Hijriyyah where the hadith at that time did not develop at all. And the revival phase in this century lasted from the 14th century until now. And the development of hadith studies began to bloom again after the awareness of Muslims emerged at that time, because they saw that orientalists studied a lot of hadiths and produced works that were often controversial. By looking at the various hadith controversies that had been raised by these orientalists, so that the awareness of Muslims The study of hadith began to emerge and continues to develop to this day.